THE EXPANSION OF JAMA’AH TABLIGH MOVEMENT AND ITS INFLUENCE ON THE RELIGIOUS BELIEF OF THE BAJO PEOPLE IN SOUTH EAST SULAWESI (State Islamic University (UIN) of Sunan Ampel Surabaya, 2020)
Jama‘ah Tabligh came to Southeast Sulawesi in the first decade of this century and soon spread among the Bajo people in the province. It’s developed and contributed to the Bajo people in a significant way. This article describes the reason behind the expansion and the influence of Jama‘ah Tabligh on them. Using historical approach, this study finds that the Bajo people accept Jama‘ah Tabligh for some peculiar reasons. They are attracted to Jama‘ah Tabligh because of effective and persuasive da‘wah launched by this Islamic group. In addition, Jama‘ah Tabligh seems to be the only Islamic da’wah that operate at the grassroots level in the region, which facilitates local curiosity to know more and finally join the movement. The non-political nature of Jama‘ah Tabligh also helps bolster the immediate acceptance of Jama‘ah Tabligh by the Bajo people. Jama‘ah Tabligh has transformed the Bajo people in many ways, allowing them to become more orthodox due to its puritan nature. The Bajo people then no longer practice syncretic religious rituals. They do not speak their vernacular language anymore and they put on thawb and turban as their clothing. Nonetheless, Jama‘ah Tabligh also brings about the teachings that are objects of criticism, namely khuruj and fatalism.